P57 Global recruitment for the RESECT study (transurethral REsection and Single-instillation intravesical chemotherapy Evaluation in bladder Cancer Treatment) - an international observational cohort study aiming to improve the quality of surgery for non-muscle invasive bladder cancer. (8th April 2021) - Lam, C M; Gallagher, K; Bhatt, N; Clement, K; Zimmermann, E; Shah, T; Khadhouri, S; Kulkarni, M; Gao, C; Light, A; Jayaraajan, K; Asif, A; et al.
Abstract: Introduction: Non-muscle invasive bladder cancer (NMIBC) is one of the most expensive cancers to treat, driven by high recurrence rates and disease progression. Mortality rates in the UK for all bladder cancers have remained relatively stable over the past decade. NMIBC can be curatively treated with transurethral resection of the bladder tumour (TURBT). Despite international evidence-based guidelines on the TURBT procedure and postoperative single instillation of mitomycin-C, TURBT quality continues to vary widely. RESECT will be the first ever international study of TURBT surgery evaluating the achievement of TURBT quality indicators globally and assessing if audit and performance feedback can improve surgical outcomes. Methods: RESECT is a prospective, multicentre international observational cohort study. Collaborators at each site will collect data using REDCap about local TURBT practice, early recurrence rates and the experience of local TURBT surgeons. The primary outcome is the rate of achievement of key TURBT quality indicators. Advertisement for the study launched in 2020. Results: As of October 1st, 2020, 524 collaborators have registered to participate. Collaborators represent 334 centres from 54 countries, with the highest number of centres from the United Kingdom (133), Spain (17), and India (16). 50.8% are trainees, 30.3% consultants, and 17.2% medical students. Based on current registrations, patient recruitment will far exceed initial projections and considerably improve statistical power. Conclusion: RESECT has attracted many collaborators internationally from consultants and trainees at all stages. RESECT has significant potential to positively impact TURBT practice, health economics and ultimately improve outcomes for patients with NMIBC globally.